Effects of M & E Planning Process on Performance of County Government Funded Water Projects in Kisii County, Kenya - Miombe, Mary; Kwasira, Josephat; Lango, Benard (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: Project Monitoring and Evaluation (M&E) is a critical component of the project management phase, which if not properly handled, may lead to project failure. Currently, Kenya faces transitional challenges from a centralized state to devolved governance system. This has prefigured both challenges and opportunities. The decentralized form of governance has exerted pressure on especially the performance of government water departments in funded water projects in counties. Despite this need most county governments initiate water projects without putting into consideration the importance of having effective M&E frameworks. One aspect that has not been given much consideration is effective implementation of M&E systems as advised by M & E experts. The aim of the study was to analyze the effect of M & E Planning process on performance of county government funded water projects in Kisii County Methodology: The study will adopt a descriptive survey design. The study target population includes 201 county water staff managing 90 water projects across the county. The census method was used to research the 201 staff involved in water projects. The primary data was collected by use of questionnaires and Key Informant interviews. Quantitative data was analyzed by employing descriptive statistics and inferential analysis, and the results were presented by tables and figures. Whereas, qualitative data was done through narrative analysis and presented in form of verbatim and narrations. Findings: M&E planning enables the construction of a logical framework that acts as a roadmap guiding the project's progress and allowing the stakeholders to understand the relationships between different project elements. The positive effect of M&E planning on project implementation affirms the pivotal role of this planning process in guiding and optimizing the execution of water-funded projects in Kisii County. Unique Contribution to Theory, Practice and Policy: This study was anchored in the program theory. Project managers and policymakers should emphasize the importance of these planning components, recognizing them as integral drivers of project success. Furthermore, capacity-building initiatives focusing on these planning aspects can further enhance the efficiency and effectiveness of M&E planning practices.